Under one roof: A study of simultaneously managed hedge funds and funds of hedge funds - Vikas Agarwal; Yan Lu; Sugata Ray (University of Cologne, Centre for Financial Research (CFR), 2014)
We examine the simultaneous management of hedge funds and funds of hedge funds. Hedge fund firms can choose to simultaneously offer a fund of hedge funds. Similarly, fund of hedge fund firms can simultaneously offer a hedge fund. We find that while superior past performance and larger size drive the decision to become simultaneous for hedge fund firms, past flows drive the decision for funds of hedge fund firms. The effects of simultaneity are also different. When hedge fund firms start funds of hedge funds, we find evidence of value creation, driven by better management of economies of scale and cross learning. In contrast, fund of hedge fund firms starting hedge funds destroy value due to expansion beyond core competencies and agency problems. We find that firms learn about their competencies in the two business lines and discontinue underperforming simultaneity arrangements to focus on the business where they perform better.
Keywords: 330